Design energy input spectra for moderate seismicity regions. - Benavent-Climent, A. (Earthquake engineering & structural dynamics.)
This paper proposes energy input spectra applicable to seismic design of structures located in low-to-moderate seismicity regions. These spectra represent the load effect, in terms of input energy, of the most severe earthquake that the construction might encounter during its lifetime. The spectra have been derived through dynamic response analyses of over 100 ground motion records obtained from 48 earthquakes that have occured in Spain. An empirical equation for estimating the energy input contributable to damage from the total input energy is also suggested. This equation takes into account both the damping and the degree of plastification of the structure. Finally, the proposed design energy input spectra are compared with the provisions of the current Spanish Seismic Code and with the response spectra of recent earthquakes that have occured in Turkey and Taiwan.